1982
DOI: 10.1037/0096-1523.8.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in rate of visual information processing.

Abstract: Each of four groups of 12 subjects performed four psychophysical tasks. The age ranges of the four groups were 19-31, 45-57, 58-70, and 71-83 years, respectively. All four tasks required some form of visual information processing: Two were backward-masking tasks; two were temporal-integration tasks. In all four tasks increasing temporal functions over age were obtained, suggesting slower processing rates as age increased. The results support an active processing model of visual perception that interprets durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 33 publications
2
50
1
Order By: Relevance
“…One potential factor is age-related diminishing of retinal illumination, which reduces the intensity of the proximal stimulus (39) and, therefore, increases visual persistence, which is known to increase as the intensity of the inducing stimulus decreases (40)(41)(42). Factors other than aging optics have also been suggested (37,38,43). In this study, we found that the duration of iconic memory, unlike that of visual persistence, decreased with age.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential factor is age-related diminishing of retinal illumination, which reduces the intensity of the proximal stimulus (39) and, therefore, increases visual persistence, which is known to increase as the intensity of the inducing stimulus decreases (40)(41)(42). Factors other than aging optics have also been suggested (37,38,43). In this study, we found that the duration of iconic memory, unlike that of visual persistence, decreased with age.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…34). In the literature on aging, visual persistence has been found to generally increase with age (35)(36)(37); also see ref. 38).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This was done in order to prevent the participant from using the first pulse pairs to guide judgments of the whole train and for compelling stimulus processing at other than pure persistence levels (Di Lollo, Arnett, & Kruk, 1982). The participant was instructed that the first pulse informed that the train was about to begin.…”
Section: Rate Of Information Segregation (Ris)mentioning
confidence: 99%
“…In such cases, the interstimulus gap might be regarded as a third event that makes it apparent that two stimulus events, rather than one, have occurred. In order to detect the gap between two visual stimuli, normal adults require an lSI of 50-55 msec (DiLollo, Arnett, & Kruk, 1982). In order to detect the gap between two auditory stimuli, normal adults require thresholds from approximately 5 to 16 msec (depending on the frequency ofthe stimulus) (Werner, Marean, Halpin, Spetner, & Gillenwater, 1992).…”
Section: Analysis Of Sequential Processingmentioning
confidence: 99%